Consumers’ Willingness to Purchase Imported Cherries towards Sustainable Market: Evidence from the Republic of Korea - Shin, S.; Ji, S. (MDPI, 2021)
Globalization has led diverse stakeholders to join the market and has resulted in corporate and product diversification; however, some markets remain monopolized by a few countries owing to “shadow trade barriers” influencing willingness to purchase. The Korean cherry market has grown rapidly since 2000 but is monopolized by U.S. cherries, which makes the market unsustainable; however, Uzbekistan cherries are 1.75-times less expensive than U.S. cherries. We examined the potential of Uzbekistan cherries to replace U.S. cherries as cherries are imported only from these countries during the spring–summer season. After collecting data through a web survey, we conducted logistic regression analyses to investigate what specific factors affect Korean consumers’ willingness to purchase Uzbekistan cherries over U.S. cherries: price perception, brand familiarity, perceived risk, and country of origin. Results showed that the more price awareness (price perception), experience (brand familiarity), and higher confidence of safety (perceived risk) that consumers had, the more they were willing to purchase Uzbekistan cherries. Consumers who checked the country of origin were less likely to purchase Uzbekistan cherries. The results provide useful information for exporters, importers, researchers, decision-makers, and policymakers concerning the utilization of products for sustainability in a monopolized market.